Newswriter's handbook an introduction to journalism - Stein, M. L. (Ames Blackwell Pub, 2006)
Reflecting the fast-changing world of print journalism, the Second Edition of Newswriter's Handbook: An Introduction to Journalism is fully updated and expanded. Authors and experienced journalists Stein, Paterno, and Burnett have refined this edition to more fully address contemporary issues. Coverage includes greater emphasis on recent legal trends involving journalism; the ethical scandals that in recent years have strained the credibility of news organizations large and small; a new section on obituary writing; and increased attention to opportunities on the World Wide Web. From spot or hard news to features, news features, editorials and opinions, the Newswriter's Handbook shows how to develop news judgment, how to write accurately and fairly, how to organize a story and write it clearly, how to handle the complexities of honesty and ethics in journalism, and how to cover traditional beats and prepare to specialize. Loaded with examples from the largest dailies to respected state capital city newspapers and campus publications, Newswriter's Handbook, Second Edition teaches students the writing and reporting skills necessary in today's job market while exciting them about the possibilities of a career in the news business.
Includes bibliographical references (p. 311-312) and index.
Keywords: Journalism--Vocational guidance